PENGEMBANGAN MODUL AJAR BERDIFERENSIASI DENGAN MODEL PEMBELAJARAN BERBASIS MASALAH PADA MATERI BILANGAN BULAT DI KELAS VII MTs NEGERI 1 PONTIANAK - Nurfadilah, Desi; Fadillah, Syarifah; Astuti, Reni (JURNAL LENTERA [PENDIDIKAN PUSAT PENELITIAN LPPM UM METRO], 2024)
The research method used in this research is development research or also known as Research and Development (R&D) research. The stages of developing teaching modules use the ADDIE model which stands for analysis, design, development, implementation and evaluation. Sampling used purposive sampling technique. The subjects of this research were class VII students at MTs Negeri 1 Pontianak. The instruments used were media and material expert validation sheets, teacher and student response questionnaires, and post-tests. The validity results reached an average of 81.2% including the "very valid" category and the validity of the material reached an average of 80.9% including the "very valid" criteria. The level of practicality of the problem based learning model differentiation teaching module on integer material for class VII MTs Negeri 1 Pontianak through the teacher response questionnaire obtained an average of 87.5% and the average student response questionnaire was 87.29%. with the criteria "very practical". The level of effectiveness of the differentiation teaching module with a problem based learning model on integer material through posttest results reached an average of 85.29% with the criterion of "very effective". Students' abilities after implementing the differentiated teaching module, seen from the posttest scores, showed that there was a significant difference with a sig value of 0.007 < 0.05.